2013
DOI: 10.1002/grl.50717
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of satellite remote sensing observations of low ozone events in the tropical upper troposphere and links with convection

Abstract: [1] Satellite observations from three instruments (Microwave Limb Sounder, Optical Spectrograph and Infrared Imaging System, and Atmospheric Chemistry Experiment Fourier Transform Spectrometer) reveal coherent patterns of low ozone events (<20 ppb) in the tropical upper troposphere. Using a chemical transport model (GEOS-Chem), we find that these events result from deep convective processes that rapidly transport air with low ozone concentrations from the marine boundary layer. These events occur with greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Spread in % of relative differences with respect to ozonesonde profiles for GOMOS V6 (left) and GOMOS ALGOM2s retrievals (right). Cooper et al, 2013;Kunze et al, 2010;Liu et al, 2009;Manney et al, 2011;Sioris et al, 2014). As observed in Fig.…”
Section: Validation Against Ozonesondessupporting
confidence: 59%
“…Spread in % of relative differences with respect to ozonesonde profiles for GOMOS V6 (left) and GOMOS ALGOM2s retrievals (right). Cooper et al, 2013;Kunze et al, 2010;Liu et al, 2009;Manney et al, 2011;Sioris et al, 2014). As observed in Fig.…”
Section: Validation Against Ozonesondessupporting
confidence: 59%
“…The MJO can also impact the tropospheric ozone, especially near the Equator (e.g., Ziemke and Chandra, 2003;Ziemke et al, 2007;Cooper et al, 2013). It was found that the equatorial tropospheric column ozone as well as equatorial upper tropospheric ozone decreases during the enhanced phase of MJO events indicating that the MJO can directly impact the equatorial tropospheric column ozone and upper tropospheric ozone.…”
Section: Introductionmentioning
confidence: 95%
“…While the influence of stratospheric intrusions on tropospheric ozone and other trace constituents have been the focus of several studies [Tsutsumi et al, 1998;Lamarque et al, 1996;Cooper et al, 2013Cooper et al, , 2005Baray et al, 2000;Rondanelli et al, 2002;Langford et al, 2012;Stohl et al, 2000;Esler et al, 2001Esler et al, , 2003Waugh and Funatsu, 2003], the influence of these intrusions on tropospheric water vapor has received somewhat less attention. Yoneyama and Parsons [1999] was one of the early studies to explicitly link extremely dry air in the tropical troposphere to midlatitude Rossby wave breaking.…”
Section: Introductionmentioning
confidence: 99%